2019
DOI: 10.13169/islastudj.5.1.0061
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Indonesian Youths toward Islamophobia: An Exploratory Study

Abstract: Islamophobia has been on the rise in the twenty-first century. Muslims from all over the world has been subjected to prejudice, hatred and fear based simply on their perceived religious affiliation. This is the new reality facing Muslims especially those living in the West. Scholars have debated this issue from the historical development of Islamophobia to the mistakes policymakers made in dealing with Islamophobia. It has been found that Islamophobia is the product of a systematic attack on Islam and Muslims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…(2014) found that in Europe and US, political conservatism was the main reason behind negative attitudes to Muslims and Islam. Shukri (2019) found that in Indonesia, Islamophobia was caused by rising Islamist extremism in that country. MacDonald (2015) demonstrated that misinformation about Islam was one of the crucial factors for the development of Islamophobic views.…”
Section: Resultsmentioning
confidence: 99%
“…(2014) found that in Europe and US, political conservatism was the main reason behind negative attitudes to Muslims and Islam. Shukri (2019) found that in Indonesia, Islamophobia was caused by rising Islamist extremism in that country. MacDonald (2015) demonstrated that misinformation about Islam was one of the crucial factors for the development of Islamophobic views.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent trial of moderasi beragama was the Ahok's case in 2017. As often found in Western countries where Islamophobia collides with racial issues (Lauwers, 2019), the Ahok's case incited Islamophobia, particularly among the minority Chinese Indonesian and Christians (Shukri, 2019). Popularly known as Ahok, the Chinese Indonesian and Christian politician Basuki Tjahaya Purnama once served as the vice governor of Jakarta and later as the governor as Joko Widodo was elected president in 2014.…”
Section: Altogether These Concerns Inflamed An Opposition Towardsmentioning
confidence: 99%
“…This condition happened because Indonesian terrorist groups used Islamic symbols and appearances while committing the terror act. 21 Post-Suharto's government also kept a legacy of seeing the Islam movement as a political threat. It could be seen when the Indonesian government banned two Islamic political groups called Hizbut Tahrir and Front Pembela Islam (Islamic Defender Front) respectively in 2017 and 2020 22 where both groups emphasise the unification of Muslims in Indonesia as a political group against corrupt government 23 .…”
Section: Political Economy Analysis (Pea)mentioning
confidence: 99%
“…51 The emergence of ISIS, the establishment of several Indonesian terrorist groups such as Jemaah Anshar Daulat and Jemaah Anshar Khilafah followed by terror acts, and the number of Indonesian combatants who flew to Syria, create Islamophobia within society although Indonesia is well-known as the most populous Muslim country. 52 Islam is then seen as an extreme religion that teaches hatred towards people outside Islam and spreads the notion of violence because terrorists use Islamic attributes while committing terror acts. Moreover, Islamophobia symptoms are shown intensely in social media 53 , curriculum in elementary education 54 and even political movements 55 .…”
Section: Harm Analysismentioning
confidence: 99%